Hi SlowlyFading!

Clicking on your LaTex I think I can see what the problems look like:

1) (21x^3+14x)/7 = 21x^3/7 + 14x/7 = ?

2) (3(2x-3)-x(2x-3))/(2x-3) = 3(2x-3)/(2x-3) - x(2x-3)/(2x-3) = ?

3) ((x^2(5x+6)-3(5x+6))/(5x+6) = x^2(5x+6)/(5x+6) - 3(5x+6)/(5x+6) = ?

In each of these we are dividing the denominator into each of the two terms. Then in

each of these cancel to obtain the final answer.

Or you can take the original numerators and factor them and then cancel:

1) 7x(3x^2+2)/7 = ?

2) (2x-3)(3-x)/(2x-3) = ?

3) (5x+6)(x^2-3)/(5x+6) = ?

The first approach is probably easier.

Can you take them from here?